Indigenous perceptions and adaptive responses to the impacts of climate variability in the Sierra Nevada de Santa Marta, Colombia - Guáqueta-Solórzano, Victoria-Eugenia; Postigo, Julio C. (Frontiers in Climate, 2022)
Indigenous Peoples worldwide are exposed to a wide range of climate threats that generate a broad spectrum of risks to their well-being. The exposure, risks, and impacts of climatic changes are most acute for marginalized and disenfranchised groups, particularly Indigenous Peoples. This paper examines Arhuaco Indigenous perceptions of climatic variability, the impacts of this variability, and the response to such impacts. The empirical basis of the paper is the fieldwork on four Arhuaco settlements in the Sierra Nevada de Santa Marta, Colombia. We gathered data through surveys, semi-structured interviews, and focus groups. The results of our qualitative and quantitative analysis are: 1) Indigenous perception of climatic variability is consistent with meteorological data; 2) Loss of traditional crops is the most relevant impact; 3) Social and cultural capitals are the most used for adaptation strategies to climate variability; and 4) vulnerability results from non-climatic factors which shape the response capacity to environmental change. Insights from our work contribute to understanding the linkages among climate, capital, and adaptive response from marginalized groups in Western society. Finally, policies to improve adaptation and strengthen the resilience of Indigenous Peoples to climate change and variability can derive from these results.